Development of hydrogels for regenerative engineering - ALARÇİN, EMİNE (WILEY-V C H VERLAG GMBH, 2017)
The aim of regenerative engineering is to restore complex tissues and biological systems through convergence in the fields of advanced biomaterials, stem cell science, and developmental biology. Hydrogels are one of the most attractive biomaterials for regenerative engineering, since they can be engineered into tissue mimetic 3D scaffolds to support cell growth due to their similarity to native extracellular matrix. Advanced nano- and micro-technologies have dramatically increased the ability to control properties and functionalities of hydrogel materials by facilitating biomimetic fabrication of more sophisticated compositions and architectures, thus extending our understanding of cell-matrix interactions at the nanoscale. With this perspective, this review discusses the most commonly used hydrogel materials and their fabrication strategies for regenerative engineering. We highlight the physical, chemical, and functional modulation of hydrogels to design and engineer biomimetic tissues based on recent achievements in nano- and micro-technologies. In addition, current hydrogel-based regenerative engineering strategies for treating multiple tissues, such as musculoskeletal, nervous and cardiac tissue, are also covered in this review. The interaction of multiple disciplines including materials science, cell biology, and chemistry, will further play an important role in the design of functional hydrogels for the regeneration of complex tissues.
Keywords: Biofabrication; Hydrogel; Nanotechnology; Regenerative engineering; Tissue regeneration; FIBROBLAST-GROWTH-FACTOR; STEM-CELL BEHAVIOR; EXTRACELLULAR-MATRIX; BONE TISSUE; INJECTABLE HYDROGEL; PEG HYDROGEL; IN-VITRO; PROTEOLYTIC DEGRADATION; ELECTROSPUN NANOFIBERS; POLY(ETHYLENE GLYCOL)